2011
DOI: 10.3851/imp1804
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase of 2007–2008 Influenza A(H1N1) Viruses Shows Increased Affinity for Sialic Acids Due to the D344N Substitution

Abstract: The D344N substitution, by modifying the enzymatic property of the N1, may have favoured the emergence and spread of viruses naturally resistant to oseltamivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…This finding has been previously reported in a study investigating the NA enzymatic properties of seasonal H1N1 virus (54) and also identified the D344N substitution among H1N1 viruses circulating in 2007-2008 as the major determinant for increased affinity to sialic acids (55). The uniqueness of Brisbane-like NA has been described in other studies, including the identification of secondary mutations (4) or epistatic mutations (39) that may restore the NA function upon acquisition of the H275Y NA mutation.…”
Section: Discussionmentioning
confidence: 54%
“…This finding has been previously reported in a study investigating the NA enzymatic properties of seasonal H1N1 virus (54) and also identified the D344N substitution among H1N1 viruses circulating in 2007-2008 as the major determinant for increased affinity to sialic acids (55). The uniqueness of Brisbane-like NA has been described in other studies, including the identification of secondary mutations (4) or epistatic mutations (39) that may restore the NA function upon acquisition of the H275Y NA mutation.…”
Section: Discussionmentioning
confidence: 54%
“…Only by the addition of secondary permissive NA substitutions was viral fitness restored for seasonal H1N1 influenza A viruses, leading to their spread worldwide (73)(74)(75). It was reported that the viruses involved in outbreaks of H274Y-containing H1N1pdm09 influenza A viruses possessed permissive secondary NA substitutions that also enhanced viral fitness (76,77).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same NA H274Y amino acid substitution severely diminished the fitness of seasonal influenza A (H1N1) viruses (60). Only the accumulation of secondary permissive NA substitutions (R222Q, V234M, and D344N; N1 numbering) favored higher NA activity and affinity, increased NA cell surface expression, and restored virus fitness (13,61) (63)(64)(65). Indeed, of the five studies that passaged influenza B virus in the presence of a NAI, all five identified HA substitutions in addition to NAI resistance-associated NA substitutions (56-58, 66, 67).…”
Section: Discussionmentioning
confidence: 99%